Structural reforms to boost growth and living standards in Argentina - González Pandiella, Alberto (OECD Publishing, 2018)
Over the last decades Argentina's living standards have lost ground relative to other developed and emerging economies. Putting Argentina on a path to stronger, inclusive and job-rich growth requires boosting productivity and strengthening investment through wide-ranging structural reforms. Areas that require reforms include the regulation of product and labour markets, taxes, infrastructure, skills, innovation, trade policy, rule of law and financial markets. Beyond changing the rules, implementation and restoring institutional capacity are equally important. Enhancing competition, for which implementation and institutions are particularly relevant, would stimulate private investment, facilitating the creation of new firms and jobs, and would bring benefits to consumers through lower prices. Finding the right packaging and sequencing of reforms is important to exploit synergies across different areas, to manage trade-offs and to protect the vulnerable from the costs of adjustment. In this context, improving active labour market policies and training can support workers in acquiring new skills and in getting ready for new jobs, improving their capacity to adjust to a changing economy
Keywords: Economics; Argentina